Disentangling Multiple Effects on Excited‐State Intramolecular Charge Transfer among Asymmetrical Tripartite PPI‐TPA/PCz Triads. Issue 4 (4th December 2020) - Yang, Sirui; Cao, Chen; Islam, Amjad; Sun, Shanshan; Deng, Ziqi; Li, Jiayu; Ni, Shaofei; Tong, Qing‐Xiao; Li, Ming‐De
Abstract: By utilizing the bipolarity of 1, 2‐diphenylphenanthroimidazole (PPI), two types of asymmetrical tripartite triads (PPI‐TPA and PPI‐PCz) were designed with triphenylamine (TPA) and 9‐phenylcarbazole (PCz). These triads are deep‐blue luminescent materials with a high fluorescence quantum yield of nearly 100 %. To trace the photophysical behaviors of these triads, their excited‐state evolution channels and interchromophoric interactions were investigated by ultrafast time‐resolved transient absorption and excited‐state theoretical calculations. The results suggest that the electronic nature, asymmetrical tripartite structure, and electron–hole distance of these triads, as well as solvent polarity, determine the lifetime of intramolecular charge transfer (ICT). Interestingly, PPI‐PCz triads show anti‐Kasha ICT, and the charge‐transfer direction among the triads is adjustable. For the PPI‐TPA triad, the electron is transferred from TPA to PPI, whereas for the PPI‐PCz triad the electron is pushed from PPI to PCz. Exploration of the excited‐state ICT in these triads may pave the way to design better luminescent materials in the future. Abstract : Deeper blue : Two types of asymmetrical tripartite triads (PPI‐TPA and PPI‐PCz) were designed as deep‐blue luminescent materials with a high fluorescence quantum yield of nearly 100 %. The electronic nature of the moieties, asymmetrical tripartite structure, and electron‐hole distance of these triads, as well as the polarity of the solvent, determine the lifetimes of excited‐state intramolecular charge transfer (ICT). Interestingly, the CT direction among the triads is adjustable.